Comparison of Immunohistochemical Expression of Antiapoptotic Protein Survivin in Normal Oral Mucosa, Oral Leukoplakia, and Oral Squamous Cell Carcinoma. (20th September 2015) - Negi, Amita; Puri, Abhiney; Gupta, Rakhi; Nangia, Rajat; Sachdeva, Alisha; Mittal, Megha
Abstract : Background . Oral squamous cell carcinoma is the sixth most frequent malignant tumor worldwide and the third most common cancers in developing countries. Oral leukoplakia is the best-known precursor lesion of oral squamous cell carcinoma. The aim of the present study was to compare immunohistochemical expression of antiapoptotic protein survivin in normal oral mucosa, oral leukoplakia, and oral squamous cell carcinoma. Method . Total 45 specimens of formalin fixed paraffin embedded tissue blocks, 15 in each of the following: normal oral mucosa, leukoplakia, and oral squamous cell carcinoma were used for the study. Immunohistochemical reaction for survivin protein was performed for the 4 µ m thick histological sections taken on positively charged slides. Results . 20% normal mucosa cases, 53.33% cases of leukoplakia, and 80% of oral squamous cell carcinoma were found out to be survivin positive. One way ANOVA test indicated statistically significant difference of survivin expression between the three different groupsp < 0.001 . Conclusion . A high incidence of survivin protein expression in oral epithelial dysplasia and squamous cell carcinoma samples indicate that survivin protein expression may be an early event in initiation and progression of oral squamous cell carcinoma.